Bloodborne Infections Relevant to Dental Practice - Suhail H. Al-Amad (Elsevier, 2024)
The surgical nature of dental practice, which frequently includes a combination of using sharp tools and the presence of blood, puts dental practitioners at a significant risk for infection with bloodborne pathogens, mainly hepatitis B, hepatitis C, and HIV. Several seroprevalence studies and case reports traced back newly diagnosed cases of hepatitis B and C to recent episodes of dental treatments. This paper provides an update on the prevalence of hepatitis B and C and HIV, the likelihood of acquiring an infection following an occupational injury, the manner in which serologic tests should be interpreted, and practical advice on ways to reduce the risk of occupational exposure.